Harvesting Fertilized Rye Cover Crop: Simulated Revenue, Net Energy, and Drainage Nitrogen Loss. Issue 1 (1st January 2018) - Malone, R. W.; Obrycki, J. F.; Karlen, D. L.; Ma, L.; Kaspar, T. C.; Jaynes, D. B.; Parkin, T. B.; Lence, S. H.; Feyereisen, G. W.; Fang, Q. X.; Richard, T. L.; Gillette, K.
Abstract : Core Ideas: Fertilizing winter rye increased estimated revenue and harvestable biomass. Fertilizing winter rye increased net energy production. Harvesting fertilized winter rye reduced simulated drainage N loss. Rye revenue in response to fertilizer rate plateaued at approximately 120 kg N ha −1 . Field studies are needed to evaluate fertilized/harvested rye cover crop. Harvesting fertilized rye ( Secale cereale L.) cover crop has been suggested as a method to increase producer revenue and biofuel feedstock production, but drainage N loss impacts are currently unknown. Using the tested Root Zone Water Quality Model (RZWQM) across several N rates, spring application of 120 kg N ha ‐1 prior to winter rye harvest reduced drainage N loss by 54% compared with no cover crop and by 18% compared with planted rye that was neither fertilized nor harvested. Estimates of producer revenue and net energy were also positive, with 8.3 Mg ha ‐1 of harvested rye biomass. If confirmed by field studies, these results suggest that double‐cropping fertilized rye is a promising strategy to increase producer revenue, increase net energy production, and reduce drainage N loss.